TAMSIL LINRUNG: GERAKAN DAN PERSEPSI MASYARAKAT TERHADAP KINERJA TAMSIL LINRUNG SEBAGAI WAKIL RAKYAT PADA MASA BAKTI 2004-2019 - Armin, Ahmad; Najamuddin, Najamuddin; Bahri, Bahri (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2024)
This research aims to analyze the movement and community response to Tamsil Linrung's performance during his tenure as a people's representative in the House of Representatives of the Republic of Indonesia 2004-2019. This research uses a qualitative method. Data collection is carried out through observation, interviews and documents by selecting informants to be interviewed with predetermined characteristics using purposive sampling techniques. The collected data is analyzed using thematic analysis. The results of the study show that the Tamsil Linrung movement is a systemic movement. During his tenure, the Tamsil Linrung movement was highly structured in the context of thought and actualization. With systemic movements, it creates a positive response in society at every level of social structure. The Tamsil Movement is a stimulus then in the process it receives attention, is interpreted and accepted by the community. The resulting response is a natural translation of the community that has been impacted.